2011
DOI: 10.1080/1357650x.2010.506689
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth, Geschwind and Galaburda hypothesis, and handedness

Abstract: Geschwind and Galaburda (1985a, 1985b) suggested that the season of conception is a non-genetic random variable that may affect laterality and handedness, probably due to seasonal variations in the hormonal influences on the foetal brain. According to this suggestion it is logical to expect seasonal anisotropy in the incidence of birth of right- and non-right-handers. The present study analysed data obtained from a sample of 3182 young Bulgarians: 2825 right-handers and 357 non-right-handers. Significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Although not confirmed by other studies (85,114,159), independent reports in humans found significantly more LHs among the males born in winter (152,160). One hypothesis is that GE49CH26-Roussigne ARI 27 September 2015 14:54 seasonal variation in the mother's hormones, such as high levels of androgens during spring, could influence fetal development and contribute, together with genetic factors, to induce a left shift.…”
Section: Hormonesmentioning
confidence: 86%
“…Although not confirmed by other studies (85,114,159), independent reports in humans found significantly more LHs among the males born in winter (152,160). One hypothesis is that GE49CH26-Roussigne ARI 27 September 2015 14:54 seasonal variation in the mother's hormones, such as high levels of androgens during spring, could influence fetal development and contribute, together with genetic factors, to induce a left shift.…”
Section: Hormonesmentioning
confidence: 86%
“…In a number of studies, a stronger seasonal effect was found in males than in females (49,50). In other studies, more left-handers were found among children born in March-July (29,30,51), but in other studies in winter (49,50,52). In yet other studies, no effect of season was detected (31,(53)(54)(55).…”
Section: Environmental Effectsmentioning
confidence: 89%
“…Gene expression analysis has revealed left-right differences in the human central nervous system as early as four weeks post conception (de Kovel et al, 2017), which indicates that laterality is an innate and pervasive property of the brain. The strong skew towards right-handedness at the population level suggests that right-hand-preference is the typical or default arrangement for humans , while left-handedness may result from genetic, environmental or random perturbations that influence the central nervous system during early development (although alternatives to this view have been discussed (Nicholls et al, 2012;Searleman et al, 1989)).…”
Section: Introductionmentioning
confidence: 99%
“…However, prenatal infection by various viral, bacterial and protozoan pathogens have been found to alter the expression of various immune molecules and contribute to early development etiology of schizophrenia. Interestingly, over the past many decades, influential theoretical propositions (Geschwind-Behan-Galaburda hypothesis9,10,11) being principal among them) and evidence base (albeit not unequivocally) have compellingly linked prenatal sex hormonal status to altered immune functions 12). Collectively, such sex hormones and immune system interactions during prenatal period have been shown to modulate cerebral asymmetry (comprehensively reviewed in the article of Stoyanov et al13)).…”
Section: Introductionmentioning
confidence: 99%